THE PULSE OF THE CITY: ’GOUARIR’ STREET AND THE EVOLUTION OF PUBLIC SPACES IN ALGERIA - Farida Sehili (International Journal of Innovative Technologies in Social Science, 2024)
The transformation of a neighborhood street into a city-wide street reflects the adaptation of urban forms to new usages, evolving as a space of urbanity where animation and social activity develop. Often located on the public domain, the street differs from the layout of plots, which is constantly changing, its underground infrastructure transforming as networks evolve. In this regard, the concept of the street needs to be assessed in light of the transformations induced by the new urban trends in Algeria. The study of the various urban and architectural transformations of “rue Gouarir” in Bordj Bou Arreridj and its evolution enables us to examine both urban recompositions as an expression of changing patterns of life, and the significance of place in contemporary Algerian cities. This study, conducted from an interdisciplinary perspective involving architecture, urban planning and economics. The aim is to assess the urban transformations and dynamics affecting this street and the people who live on it and build it. In order to better understand the dynamics of street transformation into public space, an analytical method mainly founded on socio-spatial investigation was employed. As a result, “Rue Gouarir” is overseen by community residents and business proprietors, with a conspicuous lack of involvement from local authorities. The interactions within “Rue Gouarir” have substantially transformed the surrounding area, propelling it to become a sought-after and attractive district within the city.